2010
DOI: 10.1097/mpg.0b013e31819de85d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Associations and Laboratory Abnormalities in Children With Moderate and Severe Dehydration

Abstract: Serum urea, creatinine, sodium, potassium, and glucose were useful independently in augmenting clinical examination to diagnose the degree of dehydration status among children presenting with gastroenteritis. Serum urea performed the best among all. On the contrary, none of the examined historical clinical patterns could be correlated to the dehydration status. Larger and multicenter studies are needed to validate our results and to examine their impact on final outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
4
19
1
2
Order By: Relevance
“…None should be used for indiscriminate treatment by the numbers (5,16). Complementary use of the empirical equations and userfriendly graphics may, however, aid in discerning the quantity and quality of body water losses and thus better inform (16) the heuristic treatment (5,8,(11)(12)(13)(14) of dehydration. Finally, we recognize the possible confusion of strictly misinterpreting 1-p (23,24), but consider that this approach provides benefit if the result is a clinical tool which can be more easily understood (26,27) and applied (1,22,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None should be used for indiscriminate treatment by the numbers (5,16). Complementary use of the empirical equations and userfriendly graphics may, however, aid in discerning the quantity and quality of body water losses and thus better inform (16) the heuristic treatment (5,8,(11)(12)(13)(14) of dehydration. Finally, we recognize the possible confusion of strictly misinterpreting 1-p (23,24), but consider that this approach provides benefit if the result is a clinical tool which can be more easily understood (26,27) and applied (1,22,25).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and management often require heuristic evaluation and treatment decisions can have important medical implications (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Recent research (1) described the biological variation and diagnostic threshold values for several common markers of dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated blood urea or urea nitrogen, creatinin, base excess, uric acid, serum anion gap and urine-specific gravity as well as decreased pH and bicarbonate concentration have been associated, albeit not pathognomonically, with severe dehydration [45][46][47][48]. Despite the efforts of different research groups, there is no exclusive laboratory test, nor accurate cut-off values that can be used as a sole marker of severe dehydration [14].…”
Section: Rationale For a Diagnostic Work-upmentioning
confidence: 99%
“…Hayajneh WA et al (9) found that serum urea, creatinine, sodium, potassium, and glucose were useful independently in children presenting with gastroenteritis, and serum urea was found to be the best among all. King et al (7) indicated that serum electrolytes assessment is not necessary for acute diarrhea.…”
Section: Discussionmentioning
confidence: 99%